Le contrat individuel de travail dans les nouveaux codes du travail des pays francophones d'Afrique - Visisombat, K. (Revue internationale du travail, 1968)
Article commenting on 1952 labour legislation in respect of labour contracts in french-speaking countries of Africa South of Sahara - covers provisions in respect of layoff, dismissal, severance pay, etc.
Keywords: Africa south of Sahara; Dismissal; Labour contract; Labour legislation; Layoff; Severance pay